Is fairness intuitive? An experiment accounting for subjective utility differences under time pressure - Anna Merkel; Johannes Lohse (University of Heidelberg, Department of Economics, 2018)
Evidence from response time studies and time pressure experiments has led several authors to conclude that "fairness is intuitive". In light of conflicting findings we provide theoretical arguments showing under which conditions an increase in "fairness' due to time pressure indeed provides unambiguous evidence in favor of the "fairness is intuitive" hypothesis. Drawing on recent applications of the Drift Diffusion Model (Krajbich et al., 2015a), we demonstrate how the subjective diffculty of making a choice affects decisions under time pressure and time delay, there by making an unambiguous interpretation of time pressure effects contingent on the choice situation. To explore our theoretical considerations and to retest the "fairness is intuitive" hypothesis, we analyze choices in two-person binary dictator and prisoner's dilemma games under time pressure or time delay. In addition, we manipulate the subjective difficulty of choosing the fair relative to the selfish option. Our main finding is that time pressure does not consistently promote fairness in situations where this would be predicted after accounting for choice difficulty. Hence, our results cast doubt on the hypothesis that "fairness is intuitive".
urn:nbn:de:bsz:16-heidok-245036
Keywords: 330; distributional preferences; cooperation; time pressure; response times; cognitive processes; drift diffusion models